Efficacy of Malaysian plant extracts in preventing peroxidation reactions in model and food oil systems - Jaswir, Irwandi; Hassan, Torla; Mohd Said, Mohd Zaki (Japan Oil Chemists' Society, 2004)
A study was conducted to investigate the antioxidative behaviour of the crude extracts of pegaga (Centella asiatica) leaves, and limau purut (Citrus hystrix) leaves, peels, and stems in palm olein system and in a linoleic acid model system. The antioxidative capacities of these local plants were then compared to the activity of rosemary and sage, two types of antioxidant commonly found in the market. From the analysis using Oxigen Consumption Method, it was found that among the samples evaluated, pegaga leaves had the longest time to reach the 50% oxygen in the chamber, with 90 min, meaning that this sample had the highest level of antioxidative activity. This was followed by the extracts of limau purut leaves (85 min), peels (60 min), and stems (39 min). The antioxidative activities of these plants, however, were lower than those of rosemary and sage. These commercial antioxidants were found to have 155 and 145 min time, respectively, to reach the 50% oxygen in the chamber. Results from differential scanning calorimetry (DSC) analysis showed that addition of pegaga leaves and limau purut samples to the oil in the system reduced the oxidation as evidenced by longer To of antioxidants-treated samples. Statistical analysis from this study showed that there was no significant difference between To of pegaga leaves and those of rosemary and sage. This meant that the antioxidative activity of pegaga leaves was comparable to the activities of rosemary and sage. The antioxidative activities of limau purut leaves, peels and stems were also much higher than that of control. The finding from this study indicated that all samples used in this study had very good potential to be explored as sources of natural antioxidants.